Caracteríticas de consumo de infliximab en el servicio de reumatología y dermatología 4a del hospital nacional edgardo rebagliati martins – essalud – lima, en el año 2008” - Duárez Barboza, Lidia (2009)
This study aims to determine the Characteristics of consumption of Infliximab (monoclonal antibody), in the medical service of Rheumatology and Dermatology, of the National Hospital Edgardo Rebagliati Martins (NHERM) during 2008, for which a descriptive study of cross-sectional, retrospective of medicament use. We worked with computer records of reports of infliximab used in patients hospitalized in the service of Reumatology and Dermatology at the NHERM. Given the demographics the 35.63% of consumption corresponds to female patients and 64.37% were male, according to the age group the patients 56.80% were between 30 to 49. The most common indication was ankylosing spondylitis (ICD-10 M45) with 60.34% of the total units consumed of Infliximab, the psoriatic arthritis was second (ICD-10 L40.5) with 13.79% of the total units consumed of infliximab. The average consumption expressed in DDD/100beds-day averaged 5.41, the change in the trend of consumption of Infliximab is a function of the time and this variation is statistically significant during the study period. The annual consumer cost was S /. 454248.06 nuevos soles